2014
DOI: 10.1542/peds.2013-1524
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Denys-Drash Syndrome Due to Bigenic Disease

Abstract: We report a case of Denys-Drash syndrome (DDS) in a 3-month-old girl presenting with bilateral renal cortical cysts mimicking polycystic kidney disease. Genetic analysis revealed a de novo heterozygous missense mutation c.1186G>A (p.Asp396Asn) in the WT1 gene, confirming the diagnosis of DDS. Because multiple renal cysts have never been reported in DDS, we explored several genes responsible for these renal manifestations, such as HNF-1β, PAX2, PKD1, and PKD2. Remarkably, we identified a heterozygous mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…He underwent nephrectomy of the left kidney and in the recent evaluation in 2016 his kidney function was normal. Recently, Eneman et al [2014] reported an unusual DDS patient presenting with bilateral renal cortical cysts mimicking polycystic kidney disease (PKD). They identified a de novo heterozygous missense mutation c.1186G>A (p.Asp396Asn) in the WT1 gene and a heterozygous missense variant c.12439A>G (p.Lys4147Glu) in the PKD1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…He underwent nephrectomy of the left kidney and in the recent evaluation in 2016 his kidney function was normal. Recently, Eneman et al [2014] reported an unusual DDS patient presenting with bilateral renal cortical cysts mimicking polycystic kidney disease (PKD). They identified a de novo heterozygous missense mutation c.1186G>A (p.Asp396Asn) in the WT1 gene and a heterozygous missense variant c.12439A>G (p.Lys4147Glu) in the PKD1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent syndrome was Denys-Drash syndrome in 70.8% of patients (17/24) in the present study. Denys-Drash syndrome is characterized by nephrotic syndrome owing to diffuse mesangial sclerosis, male pseudohermaphroditism, and predisposition to develop Wilms tumor and gonadoblastoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent syndrome was Denys-Drash syndrome in 70.8% of patients (17/24) in the present study. Denys-Drash syndrome is characterized by nephrotic syndrome owing to diffuse mesangial sclerosis, male pseudohermaphroditism, and predisposition to develop Wilms tumor and gonadoblastoma [11].…”
Section: Discussionmentioning
confidence: 99%